2020
DOI: 10.3390/ijerph17134873
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Presence of Company Related to Thwarted Belongingness in Real Time? Taking a Closer Look at the Conceptualization of the Construct of the Interpersonal Theory of Suicide

Abstract: (1) Background: The role of thwarted belongingness (TB) in predicting suicidal ideation, as originally assumed by the Interpersonal Theory of Suicide, is repeatedly challenged by empirical findings. This could be due to an inadequate conceptualization of the construct of TB that is assumed to be influenced by intrapersonal and interpersonal factors. (2) Methods: We examined the associations of TB with intrapersonal variables related to depression, and with interpersonal variables related to an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Thus, the contribution of TB‐7 to ideating suicide might be observed when certain risk factors have already occurred. For example, TB‐7 was relatively correlated with depression in the current sample, as some recent studies reported TB to increase in depressive states (Hallensleben et al, 2020). Additionally, TB may trigger other risk factors, including PB and hopelessness, over time (Roeder & Cole, 2019).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Thus, the contribution of TB‐7 to ideating suicide might be observed when certain risk factors have already occurred. For example, TB‐7 was relatively correlated with depression in the current sample, as some recent studies reported TB to increase in depressive states (Hallensleben et al, 2020). Additionally, TB may trigger other risk factors, including PB and hopelessness, over time (Roeder & Cole, 2019).…”
Section: Discussionmentioning
confidence: 50%
“…This suppression effect (Arah, 2008) suggests that as PB could cover up the role of TB‐7 in the subsamples, the lower levels of TB‐7 surfaced as a protective factor. Finally, as another explanation, TB has been proposed to be an acute risk factor (Bryan, Morrow, Anestis, & Joiner, 2010), which may require evaluating it as momentary incidences (Hallensleben et al, 2020). Certain populations, including geriatrics in terms of suicide attempt (Van Orden et al, 2015) and adolescents in terms of PY‐SI (Barzilay et al, 2019), seem to be more vulnerable to TB as well.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, few studies have examined predictors of within‐person, short‐term fluctuations in unmet interpersonal needs. Two studies using intensive longitudinal designs showed that, among adults with mood and psychotic disorders, being in the physical presence of others was associated with decreased perceptions of thwarted belongingness, but increased perceived burdensomeness (Hallensleben et al, 2020; Parrish et al, 2021). Another study showed that adolescents at high risk for suicidal ideation reported greater thwarted belongingness the day after negative social interactions with family members (Glenn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%